Implementasi Model Pembelajaran Scientific Learning Terhadap Kompetensi Baca Al Qur’an Mata Pelajaran Pendidikan Agama Islam Kelas X di Sma Islam Almaarif Singosari Malang - Nurun Nubuwah; Abdul Jalil; Muhammad Sulistiono (VICRATINA, 2019)
The progress and competence of human thinking is the focus of attention in the context of the current era of globalization. Related to the problem of human resources, it is inseparable from an increase in quality, we talk about education, it is very complex problems, but from some elements that support the role and quality improvement of a teacher is very high role in bringing students to achieve maximum goals aspirations for the future. The scientific learning process is a combination of the learning process which initially focuses on exploration, elaboration and confirmation supplemented by Observing, Asking, Gathering Information or trying, reasoning and communicating. The superiority of the scientific approach is expected to be able to have independence in learning and dependence on teachers must be further reduced. Independence in solving existing problems and being able to provide solutions is life skills learning for a student. After school is finished students are expected to have the ability to have strong and steady attitudes, skills and knowledge.